Storymap of the Atlas of common bean production in Africa - Castaño, Silvia Elena; Muthoni Andriatsitohaina, Rachel; Farrow, Andrew; Pineda, Sylvia-María; Gutiérrez, Daniel; Marulanda, Alejandro; Rengifo, Victoria (2020)
This storymap was created to keep together in a single online site the various products developed in relation to the Atlas of Common Bean Production in Africa-2nd edition in 2020.